ChemInform Abstract: Zintl Phases K4‐NaxSi4 (1 ≤ x ≤ 2.2) and K7NaSi8: Synthesis, Crystal Structures, and Solid‐State NMR Spectroscopic Investigations. Issue 49 (17th November 2016) - Scherf, Lavinia M.; Pecher, Oliver; Griffith, Kent J.; Haarmann, Frank; Grey, Clare P.; Faessler, Thomas F.
Abstract: K4‐x Nax Si4 (x = 1—2.2) and K7 NaSi8 are prepared by solid state reactions of stoichiometric amounts of K4 Si4 and Na4 Si4 (Ta tubes in evacuated silica tubes, 450—500 °C, 7 d; cooling rate of 0.1 °C/min).